(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
In higher educational institutions, effective management of spiritual and educational activities is crucial for fostering holistic student development. This article explores the significance of information monitoring systems in improving the management of such activities within academic settings. By integrating technology with traditional educational practices, institutions can enhance their monitoring processes to ensure a conducive environment for students’ spiritual and educational growth. This article discusses the challenges faced in managing these activities and proposes strategies to optimize information monitoring systems for better outcomes.